Back Matter JGI Des 2015 - Indonesia, Jurnal Gizi (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2015)
Author Guidelines; Reviewer Acknowledgement; Subjectand Author Indexes; Subscription form;Â dan Back Cover